Forest resource extraction by local communities: A comparative dynamic analysis - Herath M. Gunatilake; Ujjayant Chakravorty (Fondazione Eni Enrico Mattei (FEEM), 2000)
Much of the world's gene pool is located in tropical rainforests, which are being destroyed at an alarming rate. Proper management of protected forests is crucial to avoid further loss of forest resources and biodiversity. Resource extraction by local communities has been cited as a major impediment to the efficient management of protected forests. This paper develops a two sector dynamic model for agriculture and forest resource extraction which suggests that agricultural development in the periphery of protected forests may be an effective strategy for forest protection. Comparative dynamic results show that higher prices for agricultural output, lower input prices, better knowledge of agricultural production techniques and a lower rate of individual time preferences result in higher equilibrium stock of forest resources. Tobit analysis with data collected from the Sinharaja forest in Sri Lanka provides supportive empirical evidence.
Keywords: Q23; Q12; Q28; 330; Comparative dynamics; forest protection; Sri Lanka; Tobit analysis; tropical rainforests; Regenwald; Entwaldung; Landwirtschaftliche Entwicklung; Haushaltsökonomik; Theorie